Risk of venous thromboembolism in immune-mediated inflammatory diseases: a UK matched cohort study - Galloway, J; Barrett, K; Irving, P; Khavandi, K; Nijher, M; Nicholson, R; de Lusignan, S; Buch, MH (BMJ Publishing Group, 2020)
Objectives To describe the risk of venous thromboembolism (VTE), and risk factors for VTE, in people with immune-mediated inflammatory diseases (IMID) (ulcerative colitis, Crohn’s disease (CD), rheumatoid arthritis (RA) and psoriatic arthritis (PsA)), compared with a matched control population.